2018
DOI: 10.3390/md16110438
|View full text |Cite
|
Sign up to set email alerts
|

Anti-MRSA Sesquiterpenes from the Semi-Mangrove Plant Myoporum bontioides A. Gray

Abstract: The striking rise of methicillin-resistant Staphylococcus aureus (MRSA) infections has become a serious threat to public health worldwide. In an effort to search for new anti-MRSA agents from natural products, a bioassay-guided phytochemical study was conducted on the semi-mangrove plant Myoporum bontioides A. Gray, which led to the isolation of two new sesquiterpene alkaloids (1 and 2) and six known furanosesquiterpenes (3–8). Their structures were elucidated on the basis of extensive analysis of their 1D, 2D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…The MIC of the positive control vancomycin was 0.78 μg/mL. It is suggested that these two compounds can be used as new anti-MRSA drugs [ 41 ].…”
Section: Antibacterial Activity Of Different Types Of Natural Alkamentioning
confidence: 99%
“…The MIC of the positive control vancomycin was 0.78 μg/mL. It is suggested that these two compounds can be used as new anti-MRSA drugs [ 41 ].…”
Section: Antibacterial Activity Of Different Types Of Natural Alkamentioning
confidence: 99%
“…M. bontioides has been extensively investigated, the extract of which possessed a strong repellent activity against Plutella xylostella, and antifungal effect against Fusarium oxysporum, Sphaceloma fawcettii, Thielaviopsis paradoxa, Mycosphaerella sentina, Colletotrichum musae, Pestalotia mangiferae and Alternaria alternata [26,28,32], due to the presence of (−)-epingaione. It also exhibited anti-methicillin resistant Staphylococcus aureus (anti-MRSA) activity, the isolated sesquiterpene alkaloids (Myoporumine A and B) as well as epingaione and dehydroepingaione of M. bontioides also exhibited potent anti-MRSA effect with MIC values close to that of the standard vancomycin [17]. Additionally, the flavones of M. bontioides including 3,4`dimethoxy-3`,5,7-trihydroxyflavone exhibited potent antiproliferative effect against breast cancer cell line MCF-7 [24], While (2R,3R)-3,5,7-trihydroxyflavanone-3-acetate showed potent antifungal activity against Magnaporthe grisea [33].…”
Section: Biological Activities Of Myoporum Spp Secondary Metabolitesmentioning
confidence: 99%
“…Gray is native to Japan, where they are regarded as endangered plants [12,13]. Like all Myoporaceous members, Myoporum species are rich in flavonoids; and phenylethanoids; terpenoids, iridoids and alkaloid contents [3,[12][13][14][15][16][17][18][19]. Besides these secondary metabolites, most of myoporum species are characterized by secretory ducts that secrete essential oil mixture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compounds sourced from natural products (NPs) have proven to be promising in the discovery and development of novel antimicrobial drugs [ 13 , 14 ]. These compounds are obtained from living organisms, such as bacteria, fungi, plants, and marine microorganisms [ 15 , 16 ].…”
Section: Natural Products In Antimicrobial Drug Discoverymentioning
confidence: 99%